Identification and Characterisation of “Black Sticky Rice” (Oriza Sativa Glutinosa) as Photosensitizer in Development of Dye Sensitized Solar Cells (DSSC) - Agus Supriyanto; Ashari Bayu Prasada; Cari Cari; Ulfa Mahfudli Fadli (Jurnal ILMU DASAR, 2016)
It has successfully conducted a research to identify and characterize extract of black sticky rice  (Oryza Sativa Glutinosa) as photosensitizers in making of Dye Sensitized Solar Cells (DSSC). Samples were made in the sandwich structure of couple of working electrode and counter electrode. The extraction process of dye in the black sticky rice was stirred for 1 hour and then allowed to stand for 24 hours. Identification of samples using FTIR (Fourier Transform Infra-Red) to determine the chemical bond formed in the sample. Test the absorbance of the sample using UV-Visible Spectrophotometer Lambda 25 test and characterization of current and voltage (I-V) using a Keithley 2602A. The results showed maximum absorbance black rice extract appears in two peaks namely at = 324 nm and = 477 nm. While the I-V curve measurements indicate the efficiency of the resulting large black rice extract was 0.028% on a 12-hour soaking period and 0,032% in 24 hours soaking time. These results indicate that longer soaking could increase the efficiency of the resulting value.Keywords: Ketan Hitam (Oriza Sativa Glutinosa), DSSC,FTIR, UV-Vis, Keithley